Yeast Biodiversity in Vineyards and Wineries and Its Importance to the South African Wine Industry. A Review - Pretorius, I.S.; van der Westhuizen, T.J.; Augustyn, O.P.H. (South African Journal of Enology and Viticulture, 2017)
The art of winemaking is as old as human civilization and the use of yeast in this complex ecological and biochemical process dates back to ancient times. Traditionally, yeasts associated with grape berries were simply allowed to ferment the sugars to ethanol, carbon dioxide and other minor, but important, metabolites. Spontaneous fermentations are still being used in boutique wineries that depend more on vintage variability. Various microbes found on the surface of grape skins and the indigenous microbiota associated with winery surfaces participate in these natural wine fermentations. Yeasts of the genera Kloeckera, Hanseniaspora and Candida predominate in the early stages, followed by several species of Metschnikowia and Pichia (including those species that were previously assigned to the genus Hansenula) in the middle stages when the ethanol rises to 3-4%. The latter stages of natural wine fermentations are invariably dominated by the alcohol-tolerant strains of Saccharomyces cerevisiae. However, other yeasts, such as species of Brettanomyces, Kluyveromyces, Schizosaccharomyces, Torulaspora and Zygosaccharomyces also may be present during the fermentation and can occur in the resultant wine. By contrast, the rule, rather than the exception, for modern wineries depending on reliable fermentation and the production of wines with predictable quality, is the use of specially selected starter cultures of Saccharomyces. However, the use of such cultures may not necessarily prevent the growth and metabolic activity of indigenous, winery associated strains of S. cerevisiae or other wild yeasts such as Kloeckera apiculata, Hanseniaspora uvarum, Candida stellata and Torulaspora delbrueckii. It is therefore clear that both spontaneous and inoculated wine fermentations are affected by the diversity of yeasts associated with the vineyard (natural habitat) and winery (man-made niche). In light of this, focused taxonomic surveys within an ecological framework are essential to preserve and exploit the hidden oenological potential of the untapped wealth of yeast biodiversity in our wine-producing regions. To achieve this, yeast taxonomists need to continue to isolate and characterize new yeast species and strains, while wine microbiologists develop improved identification techniques that differentiate more efficiently among individual strains. At the same time such biological surveys will complement strain development and the current international effort of molecular biologists to assign a biological function to the products of each of the 6000 genes identified by computer analysis of the nucleotide sequence of the 16 chromosomes of a laboratory strain of S. cerevisiae. Furthermore, only when we have a much better understanding of yeast biodeversity, biogeography, ecology and the interaction within yeast communities will we be able to optimally harness gene technology that will benefit both the wine producer and the consumer.